Efficacy and safety of immunotherapy in elderly patients with non-small cell lung cancer. (November 2019) - Galli, Giulia; De Toma, Alessandro; Pagani, Filippo; Randon, Giovanni; Trevisan, Benedetta; Prelaj, Arsela; Ferrara, Roberto; Proto, Claudia; Signorelli, Diego; Ganzinelli, Monica; Zilembo, Nicoletta; de Braud, Filippo; et al.
Highlights: Data about immunotherapy (IO) in elderly patients with Non-Small Cell Lung Cancer (NSCLC) are few. We divided our series of NSCLC patients treated with IO as follows: <70, 70–79, ≥80 year-old. We found no difference in response rate, progression free survival and overall survival. The incidence of moderate/severe adverse events was similar in the three subgroups. We confirm that IO can be a safe and effective option for elderly patients with advanced NSCLC. Abstract: Objectives: Most trials with Immune Checkpoint Inhibitors (ICIs) for Non-Small Cell Lung Cancer (NSCLC) included only small subgroups of patients aged ≥65. As NSCLC is often diagnosed in patients aged ≥70, real-world data about efficacy and safety of immunotherapy (IO) in elderly patients are essential. Materials and Methods: We retrospectively collected data about all patients with advanced NSCLC treated with IO at our Institution between April 2013 and March 2019. The patients were stratified for age as follows: <70 year-old, 70–79 year-old, ≥80 year-old. Chi-square test was used to compare qualitative variables. Survival was estimated with Kaplan-Meier method. Log-rank test was used to compare curves. Multivariate analyses were performed with Cox model. Results: We reviewed 290 cases, with a median age of 67 (range: 29–89). Patients aged<70, 70–79 and ≥80 year-old were 180, 94 and 16, respectively. Clinical/pathological variables were uniformly distributed across age classes, except for a higher rate of males (p 0.0228) and squamous histology (p 0.0071) in the intermediate class. Response Rate (RR) was similar across age groups (p 0.9470). Median Progression Free Survival (PFS) and Overall Survival (OS) did not differ according to age (p 0.2020 and 0.9144, respectively). Toxicity was comparable across subgroups (p 0.6493). The only variables influencing outcome were performance status (PS) (p < 0.0001 for PFS, p 0.0192 for OS), number of metastatic sites (p 0.0842 for PFS, p 0.0235 for OS) and IO line (p < 0.0001 for both PFS and OS). Conclusion: Advanced age was not associated to a reduced efficacy of IO in our case series. Furthermore, no toxicity concern emerged even among the eldest pts. To our opinion, ICIs should be considered irrespective of age, provided an optimal PS at baseline. Of note, IO is often the only therapeutic option applicable to these cases considering the toxicity of chemotherapy.